Emerging target discovery and drug repurposing opportunities in chordoma - Freed, Daniel M.; Sommer, Josh; Punturi, Nindo (Frontiers in Oncology, 2022)
The development of effective and personalized treatment options for patients with rare cancers like chordoma is hampered by numerous challenges. Rational repurposing of therapies approved in other indications remains the fastest path to redefining the treatment paradigm, but chordoma’s low mutational burden limits the potential impact of genomics in guiding target discovery and precision oncology efforts. As our knowledge of oncogenic mechanisms in various malignancies has matured, it’s become increasingly clear that numerous properties of cancer transcend their genomes – leading to new and uncharted frontiers of therapeutic opportunity. In this review, we discuss how the implementation of cutting-edge tools and approaches is opening new windows into chordoma biology. We also note how a convergence of emerging observations in chordoma and other cancers is leading to the identification and evaluation of new therapeutic hypotheses for this rare cancer.